Peritextual Elements in Chinese Nonfiction Picturebooks - Sunah Chung; Jongsun Wee; Sohyun Meacham (CLELEjournal, 2024)
The focus of this study was to examine the peritextual information as well as the insider/outsider status of the book creators of Chinese and Chinese American nonfiction picturebooks, aiming to evaluate the authentic quality of multicultural nonfiction picturebooks.